2018
DOI: 10.1148/radiol.2018171557
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance and Interreader Agreement of a Standardized MR Imaging Approach in the Prediction of Small Renal Mass Histology

Abstract: Purpose To determine the diagnostic performance and inter-reader agreement of a standardized diagnostic algorithm for determining the histologic type of small (<=4cm) renal masses (SRM) with multiparametric magnetic resonance imaging (MRI). Materials and Methods This single-center, retrospective, HIPAA-compliant, IRB-approved study included 103 patients with 109 SRM, resected between December 2011 and July 2015. The requirement for informed consent was waived. Pre-surgical renal MRIs were reviewed by 7 radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 29 publications
4
46
2
1
Order By: Relevance
“…Each study was reviewed on a Picture Archiving and Communications System (PACS) workstation (iSite, Philips Healthcare, Best, Netherlands). As part of the clinical, structured report, a ccLS [14,15,18] was prospectively assigned for each renal tumor identified. If multiple, a separate score was assigned to each.…”
Section: Methodsmentioning
confidence: 99%
“…Each study was reviewed on a Picture Archiving and Communications System (PACS) workstation (iSite, Philips Healthcare, Best, Netherlands). As part of the clinical, structured report, a ccLS [14,15,18] was prospectively assigned for each renal tumor identified. If multiple, a separate score was assigned to each.…”
Section: Methodsmentioning
confidence: 99%
“…Studies investigating the algorithmic diagnosis of small renal masses with MRI have noted that the presence of a microscopic fat may distinguish clear‐cell RCCs from oncocytic neoplasms (eg, chromophobe RCC and oncocytoma), each of which is characteristically hyperintense on T 2 W imaging . Clear‐cell RCC also have been shown to be more avidly enhancing compared with oncocytic neoplasms . A minority of papillary tumors also may show microscopic fat, which has been speculated to be due to clear cell heterogeneity; such tumors may be distinguished from fat‐poor AML by their high signal intensity on T 2 w imaging (compared with typical papillary RCCs) .…”
Section: Description Of Adrenal and Renal Masses By The Presence And mentioning
confidence: 99%
“…More recently, multiple institutions have reported single-center retrospective studies suggesting that CT and MR can be used to diagnose previously indeterminate specific benign (e.g., fat poor AML) and malignant (e.g., clear cell RCC) diagnoses without need of percutaneous biopsy [48, 49]. MRI is particularly well suited to subtype renal masses given the lack of ionizing radiation that complicates multiphase CT, and the multiparametric data sets obtained in standard clinical examinations.…”
Section: Accelerating the Research Missionmentioning
confidence: 99%
“…For example, it has been shown that small enhancing renal masses with homogeneous low signal intensity on T2-weighted images exhibit slower growth (i.e., tumor doubling time > 2 years) and may be better candidates for active surveillance [16]. Others have explored whether an MRI-based likelihood score of clear cell RCC histology may better identify which patients are suitable for active treatment [49]. Though promising, much of this work has been single center with relatively small datasets, especially for uncommon histologic variants.…”
Section: Accelerating the Research Missionmentioning
confidence: 99%